2011
DOI: 10.1002/ar.21418
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of the Dog Soft Palate. I. Histological Evaluation of the Caudal Soft Palate in Mesaticephalic Breeds

Abstract: The gross anatomy and overall structure of the soft palate has been described in the average dog's head, however, no descriptive microanatomical studies of the dog soft palate are available, despite their possible utility in view of the manifold and important repercussions of this organ physiology. This is the first of two companion papers, dealing with the caudal part of the soft palate in the canine species, in mesaticephalic and brachycephalic dogs. Specimens from mesaticephalic healthy dogs (N ¼ 8) were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…Histological peculiarities, such as thickened mucosal epithelia, general oedema of the connective tissue, glandular hyperplasia and many different muscular modifications were commonly described (Pichetto et al, ). On the other hand, such histological features could not be found in the corresponding part of the soft palate of mesaticephalic dog breeds as previously described in a related article (Arrighi et al, ).…”
Section: Introductionmentioning
confidence: 43%
See 3 more Smart Citations
“…Histological peculiarities, such as thickened mucosal epithelia, general oedema of the connective tissue, glandular hyperplasia and many different muscular modifications were commonly described (Pichetto et al, ). On the other hand, such histological features could not be found in the corresponding part of the soft palate of mesaticephalic dog breeds as previously described in a related article (Arrighi et al, ).…”
Section: Introductionmentioning
confidence: 43%
“…The different aspect of the mucosal layer at the two dorsal and ventral sides, together with the different organization at the boundary between epithelial tissue and the supporting connective, might sustain different functional performances at the two mucosal sides, as underlined in the mesaticephalic dog soft palate (Arrighi et al, ) and previously suggested by Paulsen and Thale () in the human soft palate.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Brachycephalic airway syndrome (BAS) is an established cause of respiratory distress in brachycephalic dog breeds . The shortened skull bones in these breeds are not accompanied by reduction of the associated soft tissue structures, resulting in a compressed nasal passage and altered pharyngeal anatomy . The most frequently reported primary components of BAS are stenotic nares and an elongated, thickened soft palate .…”
mentioning
confidence: 99%